Growth and Yield Production of Pakcoy as Influenced by Artificial Light Irradiation - Sari Widya Utami; Artdhita Fajar Pratiwi; Galih Mustiko Aji (Green Engineering Society, 2023)
Artificial light in indoor plant production is still a challenge related to the amount of electrical energy used, such as in the Pakcoy plant. The Pakcoy plant has nutritional and economic value and is usually used as a research indicator plant. This study aimed to determine the effect of artificial light irradiation on the growth and yield of Pakcoy plants. The research was conducted in a plant factory in an indoor hydroponic system, with LED light of 100 umol/m2/s as a light source for the growth of Pakcoy plants. The artificial light irradiation length treatment consisted of 4 levels, namely 12 hours/day, 16 hours/day, 20 hours/day, and 24 hours/day. The most significant growth, yield, and content of vitamin C in Pakcoy plants were obtained in maximum artificial light exposure for 24 hours/day, and the highest protein content was obtained in the long irradiation treatment for 16 hours/day.